Quy trình quản lý rơm rạ theo hướng nông nghiệp tuần hoàn và phát thải thấp ở đồng bằng sông Cửu Long - Department of Crop Production, Vietnam (Department of Crop Production, 2023)
The national technical guideline on rice straw management towards circular economy and low emission in the Mekong River Delta (MRD) was issued on 10 July 2023 by Department of Crop Production, Ministry of Agriculture and Rural Development of Viet Nam. This provides guidance on rice straw management based on the criteria: no burning rice straw, no incorporation of rice straw in puddled field, collecting straw out of the field for production of products with higher value, such as mushroom, cattle feed, bio-bedding, mulching, and composting. This technical guideline is for rice production in MRD and other regions.